SOCIAL INTERACTION OF THE SUMBEREJO NGASEM KEDIRI COMMUNITY IN DEALING WITH PEOPLE AFFECTED BY COVID-19 AS A FORM OF LIVING HADITH SILATURAHIM - Kinanthi, Shela Yudha; Dodi, Limas (RIWAYAH, 2022)
Indonesia is a country that is famous for its hospitality, both to people residing in the country as well as to foreign people from various countries. A small example here is to our fellow neighbors –people who are almost every day always encountered –whose homes are close to ours. When a neighbor passes by our house, we will automatically –or even their own –say hello. It is also becoming more common in communities that primarily reside in rural areas. When in difficult circumstances or when hit by disasters – such as a house fire, relatives with death, or even affected by Covid-19 – automatically we – humans known as social beings – will help willingly. From here human being indirectly build a relationship with each other. However, with the existence of Covid-19 that doesn't subsided from the beginning of 2020 – when it first entered Indonesia – until now, people are busy guarding themselves to prevent them from contracting Covid-19. People were faced with two tough choices, namely helping those affected by Covid-19 or better avoiding and maintaining distance so as not to be affected. However, because humans have basic characteristics as social beings as well as Indonesian society which is famous for their attitude of hospitality, the community – especially in Sumberejo Village, Ngasem District, Kediri Regency – still help each other even in the Covid-19 situation.[Interaksi Sosial Masyarakat Sumberejo Ngasem Kediri dalam Menghadapi Orang yang Terdampak Covid-19 sebagai Bentuk Living Hadith Silaturahim. Indonesia merupakan negara yang terkenal dengan keramah-tamahannya, baik kepada masyarakat yang bertempat tinggal di negara itu sendiri, maupun kepada masyarakat asing dari berbagai negara. Sebagai contoh kecil di sini adalah kepada sesama tetangga –orang-orang yang hampir setiap hari selalu dijumpai –yang rumahnya berdekatan dengan kita. Ketika seorang tetangga melewati rumah kita, maka kita secara otomatis  –atau bahkan mereka sendiri –akan menyapa. Hal ini juga menjadi lebih umum di masyarakat yang khususnya bertempat tinggal di pedesaan. Ketika dalam keadaan susah ataupun ketika tertimpa musibah –seperti rumah kebakaran, kerabat dengan meninggal dunia, atau bahkan terdampak Covid-19 –secara otomatis kita –manusia yang dikenal sebagai makhluk sosial –akan membantu dengan sukarela. Dari sinilah secara tidak langsung manusia membangun silaturahmi satu sama lain. Namun, dengan adanya Covid-19 yang tak kunjung mereda dari awal tahun 2020 –ketika pertama kali masuk di Indonesia –hingga sekarang, masyarakat sibuk menjaga diri untuk mencegah agar tidak tertular Covid-19. Masyarakat seperti dihadapkan dua pilihan berat, yakni membantu mereka yang terdampak Covid-19 atau lebih baik menghindari serta menjaga jarak agar tidak ikut terdampak. Namun, dikarenakan manusia yang memiliki sifat dasar sebagai makhluk sosial sekaligus sebagai masyarakat Indonesia yang terkenal dengan sikap keramah-tamahannya, masyarakat –khususnya di Desa Sumberejo, Kecamatan Ngasem, Kabupaten Kediri –tetap saling membantu satu sama lain di dalam situasi Covid-19 sekalipun.]